Kajian terhadap Persepsi Mahasiswa terhadap Rasisme dalam Konteks Sila Kedua Pancasila : Studi di Jurusan PPKn Unimed - Agustin Pratama Sihotang; Deo Agung Haganta Barus; Eirene Dahlia Sidabutar; Joy Prana Bangun; Nasywa Yasmin Purba; Ramsul Yandi Nababan (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Pancasila is the basis of the state that has been in effect since June 1, 1945. Pancasila is not only the basis of the state, but Pancasila is the personality of the Indoneisa nation. After that the life of the nation and the nation of the Indonesian people is regulated and adjusted by Pancasila. In the second principle, which reads "Just and civilized humanity", states the same dignity for every human being, so that there needs to be an attitude of respect, an attitude of helping, and a humanitarian attitude between individuals.With the diversity in Indonesia, it is important for Indonesian citizens to understand the insight of the archipelago and apply it in their daily lives to stop divisions in Indonesia, especially those caused by racism. By applying the values of Pancasila in our daily lives, we can avoid acts of racism.